Analisis ANALISIS HAMBATAN PESERTA DIDIK DALAM PROSES PEMBELAJARAN SECARA DARING DI SMA NEGERI 02 BUNTU MALANGKA KABUPATEN MAMASA - AKHMAD, NUR AMALIAH (Program Studi Pendidikan Fisika Unpacti Makassar, 2023)
This research was conducted to know the obstacles students face in the Brave Biology learning process at SMA Negeri 2 Buntu Malangka, Mamasa Regency, and how to solve them. The method used was a qualitative descriptive study with the research subjects being all students of class X and class XI IPA SMA Negeri 2 Buntu Malangka KAB. Mamasa. Data collection was carried out through observation, interviews, and documentation studies. The results of the study, among others, show that the obstacles faced by students in learning are lack of motivation, limited internet access, and lack of technological skills. In addition, internal factors such as the inability to manage time and the lack of ability to self-regulate are also obstacles to learning to dare. This study provides an in-depth and detailed understanding of barriers to courageous learning at SMA Negeri 2 Buntu Malangka. It can be used as a basis for decision-making or program planning in the future. One way to overcome these obstacles is to motivate students to be more enthusiastic about learning, provide training on the use of technology, and improve internet access in the regions. This study's results also show the teacher's important role in helping students overcome these obstacles and ensure that courageous learning can run well.